Análise da reconstrução da política pública de economia solidária no governo do estado do Rio Grande do Sul (2011-2012) - Damascena, Monique Bronzoni (2013)
The Solidarity Economy in Brazil has been instituted as public policy and measures taken by this policy propose other ways of organizing production, distribution and consumption, beyond those known in the capitalist system. This characteristic has repercussions in the day to day of workers who joined the Solidarity Economy and who regard it as a right that must be guaranteed institutionally. The Solidarity Economy emerged in Brazil as a coping measure or alternative to the work system. It began to take form as public policy in the final decades of the twentieth century and at the threshold of the twenty-first century, starting with transformations related to the work process. Efforts towards the Solidarity Economy, in the State of Rio Grande do Sul, first appeared in the Municipality of Porto Alegre (1996-2000), and after in the State Government (1999-2002). The parameters implemented by the State Government were in-turn used by the Federal Government in the founding of the National Secretariat for the Solidarity Economy SENAES and in its formation also formed a state branch of the secretariat to facilitate efforts at the state level.The Solidarity Economy, in the current Brazilian context, uses mediation processes of the current economic system in the promotion and encouragement of the Solidarity Economy in Brazil. The Solidarity Economy is therefore considered as the "champion of democratic solidarity" (LAVILLE; Gaiger, 2009). Given this situation, this study has aimed to analyse the measures taken for workers of the Solidarity Economy in Rio Grande do Sul, by investigating the actions of the Department of Incentive and Promotion of the Solidarity Economy - DIFESOL, a department created during the term of Tarso Genro (2011-2015) to meet the demands of Solidarity Economy throughout the State. To realize the stated objective, the research was conducted through document analysis with a qualitative approach and guided by critical-dialectical methodology. The analysis was performed by means of the documents prepared by the Department, in addition to the laws that are being followed to ensure the implementation of the policy in Rio Grande do Sul. Textual discourse analysis (Moraes, 2003) was chosen to analyse the collected data.The analysis of public policy in relation to Solidarity Economy allowed the listing of the characteristics of the policy through the actions of DIFESOL. Public policy which is comprised of strategies aimed at improving regional development strategies at the state and federal levels for Eradication of Extreme Poverty. The analysis, by means of programs, permits the understanding of a possible line of action, and possible measures of articulation, training and funding. Among the main features of this Department's activities are a focus on production chains that cover all undertakings and investments of DIFESOL and opening possibilities for carrying out other activities.